Knowledge and Current Practices in Monogenic Uveitis: An International Survey by IUSG and AIDA Network (2023)
Introduction: This study aims to explore awareness, knowledge, and diagnostic/therapeutic practices in monogenic uveitis (mU) among uveitis experts. Methods: This is an explorative, cross-sectional survey study. An anonymous, semi-structured, electronic survey was delivered to uveitis experts from the Autoinflammatory Diseases Alliance (AIDA) Network and International Uveitis Study Group (IUSG). We included respondents answering???50% of the survey. Results: Seventy-seven participants rated their knowledge of mU as proficient (3.9%), adequate (15.6%), sufficient (16.9%), or poor (63.6%). When asked about the first mU gene they thought of, 60.4% mentioned NOD2, 3.9% mentioned NLRP3 or MEFV, and 49.4% provided incorrect or no answers. Success rates in clinical scenarios varied from 15.6% to 55.8% and were higher for ophthalmologists working in multidisciplinary teams (p??0.01). Genetic testing was ordered for suspected mU by 41.6% of physicians. The availability of molecular techniques did not significantly differ based on geography (p??0.05). The public healthcare system ensured a higher percentage of tests prescribed were obtained by patients compared to private insurances (p??0.00). In terms of disease-modifying anti-rheumatic drugs (DMARDs), tumor necrosis factor-? inhibitors were the most familiar to uveitis experts. The difficulties with off-label therapy procedures were the primary barrier to DMARDs prescription for patients with mU and correlated inversely with the obtained/prescribed drug ratio for interleukin-1 (p??0.01) and interleukin-6 (p??0.01) inhibitors.Conclusions: This survey identifies proficiency areas, gaps, and opportunities for targeted improvements in patients care. The comprehensive outputs may inform evidence-based guidelines, empowering clinicians with standardized approaches, and drive an AIDA Network—IUSG unified effort to advance scientific knowledge and clinical practice.